RELATIONSHIPBETWEEN GOOD CORPORATE GOVERNANCE, LEVERAGE, COMPANY SIZE, AND FINANCIAL PERFORMANCE REGISTERED ON INDONESIA STOCK EXCHANGE - LMS Kristiyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The aim of this research is to determine the relationship between Good Corporate Governance, Leverage, and Company Size with the financial performance of banks listed on the Indonesia Stock Exchange. The variables used to measure Good Corporate Governance are institutional ownership, leverage is measured by debt to equity ratio (DER), and company size is seen from total assets. The variable used to measure the company's financial performance is return on assets (ROA). The population is as many as 20 banking companies listed on the Indonesia Stock Exchange for the period 2016-2018. The analysis technique used is multiple linear regression analysis, hypothesis testing, and classic assumption tests which include normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, with a significance level of α = 5%. The results showed that simultaneously Good Corporate Governance, Leverage, Company Size had a significant effect on financial performance. As evidenced by the results of the F test, it was found that the significance of F 0.000